2015
DOI: 10.1016/j.jval.2015.03.331
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy And Safety of Canagliflozin among Patients with type 2 diabetes Mellitus: a Systematic review and meta-analysis

Abstract: OBJECTIVES: To inform a multiple technology appraisal to be conducted by the National Institute for Health and Care Excellence on the use of agents that inhibit sodium-glucose co-transporter 2 (SGLT2), canagliflozin was assessed as monotherapy treatment for T2DM. METHODS: A systematic literature review identified 36 trials, which were used to perform a Bayesian NMA to estimate the relative efficacy (HbA1c, weight, and systolic blood pressure [SBP]) of canagliflozin monotherapy at 26±4 weeks compared to dipepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We identified 1289 unique citations, of which 47 quantitative systematic reviews met our inclusion criteria (Figure 1 and Table 1). Twenty-two reviews (47%) reported no funding sou rce, [17][18][19][20][21][22][23][24]27,28,[30][31][32]35,38,39,43,44,50,52,53,55 while nine reviews (19%) received funding from government, 25,26,29,37,40,41,51,54,59 five reviews (11%) received internal funding, [45][46][47][48][49] three reviews (6%) received foundational funding 16,34,36 and one review (2%) was funded by private industry. 57 A funding source was not disclosed in seven reviews (15%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 1289 unique citations, of which 47 quantitative systematic reviews met our inclusion criteria (Figure 1 and Table 1). Twenty-two reviews (47%) reported no funding sou rce, [17][18][19][20][21][22][23][24]27,28,[30][31][32]35,38,39,43,44,50,52,53,55 while nine reviews (19%) received funding from government, 25,26,29,37,40,41,51,54,59 five reviews (11%) received internal funding, [45][46][47][48][49] three reviews (6%) received foundational funding 16,34,36 and one review (2%) was funded by private industry. 57 A funding source was not disclosed in seven reviews (15%).…”
Section: Resultsmentioning
confidence: 99%
“…44 Twentyfour (52%) reviews were considered critically low quality, [16][17][18][20][21][22][23][24][27][28][29]32,34,[38][39][40]43,45,50,51,54,55,59,62 11 (23%) reviews were considered low quality 19,33,46,[47][48][49]52,56,57,60,61 and 11 (23%) reviews were considered moderate quality. 25,26,30,31,[35][36][37]41,42,53,55 From the 47 included reviews, there were 958 point estimates reporting on 59 unique adverse effects. The most frequently reported estimates (n = 213, 22%) were for urinary tract infection (Figure 3).…”
Section: Resultsmentioning
confidence: 99%